Blalock-Taussig anastomosis in 126 patients with Fallot's tetralogy. Issue 3 (May 1973) - Reid, J. M.; Coleman, E. N.; Barclay, R. S.; Stevenson, J. G.
Abstract : The long-term results of Blalock anastomosis in 126 patients (1954-71) for Fallot's tetralogy are presented. The operative mortality was 10% and the overall mortality 38%. The 78 survivors were reviewed after periods of surveillance ranging from six months to 17 years. Complications were few. It is concluded that although total correction as a primary procedure has become the treatment of choice in most, it may in some instances never be technically feasible because of extreme underdevelopment of the right ventricular outflow tract. In the very young with urgent symptoms and rapid deterioration total correction would be considered hazardous. In the infant a high operative mortality reflected the inadequate calibre of the vessels used in the shunt operation.